Are you what you eat? Micronutritional deficiencies during development influence adult personality-related traits. (March 2015) - Noguera, José C.; Metcalfe, Neil B.; Surai, Peter F.; Monaghan, Pat
Abstract : Stressful environmental conditions such as periods of poor nutrition have been shown to affect a variety of life history traits. Although nutrition-induced effects on the phenotype can appear through the entire life of an individual, it is becoming evident that there are sensitive periods during development when phenotypic traits have heightened sensitivity to nutritional conditions. Very few studies have investigated how nutrition can affect an important aspect of an organism's phenotype: the development of its 'personality'. In this study we manipulated the availability of the main micronutrients (i.e. vitamins and essential minerals) present in the diet of zebra finches, Taeniopygia guttata, during their postnatal development and/or during their sexual maturation. Later, once the birds were fully adult, we assessed a series of behavioural traits previously used to assess personality in birds. We found that low availability of dietary micronutrients during the postnatal period resulted in reduced boldness in males once they reached adulthood, but had no effect on adult stress responses or neophobic behaviour. No such effects were found in females. In contrast, a low micronutrient diet during sexual maturation led in both sexes to reduced stress responses and neophobic behaviours in adulthood. Interestingly, we also found that females became more aggressive as adults if they had received a low micronutrient diet during development, irrespective of when the availability of micronutrients was modified. Overall, our results demonstrate substantial effects of diet on the development of behavioural traits, and that these effects differ both between the sexes and over different developmental periods. Highlights: The effect of nutrition on different adult personality traits was investigated. Dietary micronutrients were manipulated during postnatal development. A low micronutrient diet during the postnatal period reduced male boldness. A low micronutrient diet during maturation reduced stress responses and neophobia. Female aggressiveness was always promoted by a low micronutrient diet.